Patients' preferences for selection of endpoints in cardiovascular clinical trials - Robert D. Chow; Kashmira P. Wankhedkar; Mihriye Mete (Greater Baltimore Medical Center, 2014)
Background: To reduce the duration and overall costs of cardiovascular trials, use of the combined endpoints in trial design has become commonplace. Though this methodology may serve the needs of investigators and trial sponsors, the preferences of patients or potential trial subjects in the trial design process has not been studied. Objective: To determine the preferences of patients in the design of cardiovascular trials. Design: Participants were surveyed in a pilot study regarding preferences among various single endpoints commonly used in cardiovascular trials, preference for single vs. composite endpoints, and the likelihood of compliance with a heart medication if patients similar to them participated in the trial design process. Participants: One hundred adult English-speaking patients, 38% male, from a primary care ambulatory practice located in an urban setting. Key results: Among single endpoints, participants rated heart attack as significantly more important than death from other causes (4.53 vs. 3.69, p=0.004) on a scale of 1-6. Death from heart disease was rated as significantly more important than chest pain (4.73 vs. 2.47, p<0.001), angioplasty/PCI/CABG (4.73 vs. 2.43, p<0.001), and stroke (4.73 vs. 2.43, p<0.001). Participants also expressed a slight preference for combined endpoints over single endpoint (43% vs. 57%), incorporation of the opinions of the study patient population into the design of trials (48% vs. 41% for researchers), and a greater likelihood of medication compliance if patient preferences were considered during trial design (67% indicated a significant to major effect). Conclusions: Patients are able to make judgments and express preferences regarding trial design. They prefer that the opinions of the study population rather than the general population be incorporated into the design of the study. This novel approach to study design would not only incorporate patient preferences into medical decision making, but it also has the potential to improve compliance with cardiovascular medications.